2022
DOI: 10.1038/s44161-021-00009-1
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic framework for cardiometabolic and coronary artery diseases

Abstract: yocardial infarction and stroke, the leading causes of global morbidity and mortality, are caused by atherosclerosis, which originates from inflammatory, lipid, endocrine, metabolic and hemodynamic disturbances. Indeed, multiple and parallel malfunctions in metabolic organs are responsible for the complex molecular disease processes of cardiometabolic disorders (CMDs) leading to CAD 1 . For example, the liver plays a central role in determining plasma lipid levels by regulating lipoprotein synthesis and lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 60 publications
0
93
0
Order By: Relevance
“…Subject recruitment and tissue collection in the Stockholm-Tartu Atherosclerosis Reverse Networks Engineering Task study (STARNET) were performed as previously described [ 2 , 7 10 ]. Briefly, patients with angiographically proven CAD who were eligible for open-thorax surgery and control subjects without CAD were enrolled into this institutional review committee approved protocol after written informed consent at Tartu University Hospital, Estonia.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subject recruitment and tissue collection in the Stockholm-Tartu Atherosclerosis Reverse Networks Engineering Task study (STARNET) were performed as previously described [ 2 , 7 10 ]. Briefly, patients with angiographically proven CAD who were eligible for open-thorax surgery and control subjects without CAD were enrolled into this institutional review committee approved protocol after written informed consent at Tartu University Hospital, Estonia.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed methods are provided in our prior publication [ 10 ]. In brief, R package Weighted Gene Co-expression Network Analysis (WGCNA) [ 40 ] was used to identify correlation patterns among genes across RNA-seq data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with CVDs, the STARNET database is a useful resource to study cardiometabolic diseases. Koplev and colleagues used STARNET to construct co-expression-based gene networks between cardiometabolic diseases and CAD ( 184 ). Similarly, Shu et al explored shared regulatory networks between type 2 diabetes and CVD and also identified 15 KDGs, including HMGCR, CAV1, IGF1, and PCOLCE, for both diseases ( 185 ).…”
Section: Network Medicine Paradigms For Cardiovascular Disease Researchmentioning
confidence: 99%